Structure and dynamics in low-density regions: galaxy–galaxy correlations inside cosmic voids - Ruiz, Andrés Nicolás (2019)
We compute the galaxy–galaxy correlation function of low-luminosity SDSS-DR7 galaxies (−20 < Mr − 5log10(h) < −18) inside cosmic voids identified in a volume-limited sample of galaxies at z = 0.085. To identify voids, we use bright galaxies with Mr − 5log10(h) < −20.0. We find that structure in voids as traced by faint galaxies is mildly non-linear as compared with the general population of galaxies with similar luminosities. This implies a redshift-space correlation function with a similar shape than the real-space correlation albeit a normalization factor. The redshift-space distortions of void galaxies allow to calculate pairwise velocity distributions which are consistent with an exponential model with a pairwise velocity dispersion of w ∼ 50–70 km s−1, significantly lower than the global value of w ∼ 500 km s−1. We also find that the internal structure of voids as traced by faint galaxies is independent of void environment, namely the correlation functions of galaxies residing in void-in-void or void-in-shell regions are identical within uncertainties. We have tested all our results with the semi-analytic catalogue MDPL2-SAG finding a suitable agreement with the observations in all topics studied.